Exploring the relationship between binge eating and differentiation of self: the mediating role of emotional distress and work stress - Peleg, Ora; Idan, Meirav; Katz, Ruth (Frontiers in Nutrition, 2024)
Binge Eating Disorder (BED) is a prevalent eating disorder outlined in the DSM-5. Emotional distress (including stress, anxiety, and depression) stands out as a critical risk factor for developing eating disorders, and specifically BED. Recent studies have identified differentiation of self- a family pattern involving the ability to balance emotions and cognitions, as well as intimacy and autonomy—as a factor that exacerbates emotional distress. This relationship highlights the importance of addressing both emotional distress and family dynamics in understanding BED. While associations have been found between work-related factors and family dynamics with emotional distress, there has been limited investigation into the specific risk factors that are uniquely linked to BED. It was hypothesized that differentiation of self would relate to BED symptoms through the mediation of emotional distress and work stress. A systematic sampling method was applied to select a total of 275 participants for this study, with 60% women and 40% men (aged 20–45, M = 32.71, SD = 7.50). The findings suggest that low differentiation of self may increase vulnerability to BED symptoms by increasing susceptibility to emotional distress, including stress in the workplace. In addition, the analyses indicated that women reported higher levels of BED symptoms, while men reported higher levels of differentiation of self. The study sheds light on the contribution of unregulated family and emotional patterns to BED, providing valuable insights for organizations seeking to promote healthier work environments.